2023
DOI: 10.11628/ksppe.2023.26.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Growth Characteristics of <italic>Allium microdictyon</italic> in Forest Cultivation

Abstract: Background and objective: This study was conducted to investigate the effect of the cultivation environment of <i>Allium microdictyon</i> in forest cultivation on leaf growth characteristics and antioxidant activity.Methods: One-year seedlings of <i>Allium microdictyon</i> were planted in test sites with different elevations and slopes in a forest. Each test site was selected on the south-facing slope and north-facing slope each at 700 m and 500 m above sea level, and each test site was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…According to Sorensen and Lamb [54], if too much Bc is added to the soil, crops may grow slowly due to nutrient adsorption. Yun et al [55] reported that the crop's yield decreased when >1000 kg per 10 a was applied in onion cultivation. In this study, Bc treatments reduced LWR while increasing RWR, indicating a tendency to significantly reduce the aboveground growth.…”
Section: Growth Characteristicsmentioning
confidence: 99%
“…According to Sorensen and Lamb [54], if too much Bc is added to the soil, crops may grow slowly due to nutrient adsorption. Yun et al [55] reported that the crop's yield decreased when >1000 kg per 10 a was applied in onion cultivation. In this study, Bc treatments reduced LWR while increasing RWR, indicating a tendency to significantly reduce the aboveground growth.…”
Section: Growth Characteristicsmentioning
confidence: 99%